Compounding deep sea physical impacts on marine microbial motility - Mullane, Kelli K.; Nishiyama, Masayoshi; Kurihara, Tatsuo; Bartlett, Douglas H. (Frontiers in Marine Science, 2023)
Introduction Approximately three-fourths of all pelagic marine prokaryotes live in the deep sea, an environment characterized by high hydrostatic pressure and, in most cases, low temperature. Labile organic matter is often scarce within these settings, providing a competitive advantage to motile cells that can access the nutrients within a greater seawater volume. Because many cells present at depth are shallow water-adapted microbes descending from more productive surface waters, deep-sea conditions could significantly reduce their motility and, consequently, their biogeochemical activities. Methods In this study, we address this possibility by examining the impact of deep-sea physical conditions on the motility of three representative marine microbes belonging to the cosmopolitan genera Halomonas, Alcanivorax, and Shewanella. Growth-dependent motility agar assays and growth-independent microscopy assays were employed at four pressures and two temperatures. Results At pressures equivalent to bathyal and abyssal depths (10 – 50 Megapascals), decreases in temperature (30°C – 4°C or 23°C – 7°C depending on the assay) had a greater negative impact on motility than pressure. In addition, the high-pressure and low-temperature impacts were additive. Exposure to high pressure and/or low temperature had varying degrees of effect on flagellar function, depending on the strain and the magnitude of the applied stress. These ranged from short-term impacts that were quickly reversible to long-term impacts that were detrimental to the function of the flagellum, leading to complete loss of motility. Discussion These findings highlight the sensitivity of motility systems of piezosensitive mesophilic marine bacteria to the combined pressure/temperature conditions present in the deep sea, phenotypes that in situ are likely to manifest themselves in the modulation of diverse microbial activities.